Generation of Fabry cardiomyopathy model for drug screening using induced pluripotent stem cell-derived cardiomyocytes from a female Fabry patient. (August 2018) - Kuramoto, Yuki; Naito, Atsuhiko T.; Tojo, Hiromasa; Sakai, Taku; Ito, Masamichi; Shibamoto, Masato; Nakagawa, Akito; Higo, Tomoaki; Okada, Katsuki; Yamaguchi, Toshihiro; Lee, Jong-Kook; Miyagawa, Shigeru; et al.
Abstract: Background: Fabry disease is an X-linked disease caused by mutations in α-galactosidase A (GLA); these mutations result in the accumulation of its substrates, mainly globotriaosylceramide (Gb3). The accumulation of glycosphingolipids induces pathogenic changes in various organs, including the heart, and Fabry cardiomyopathy is the most frequent cause of death in patients with Fabry disease. Existing therapies to treat Fabry disease have limited efficacy, and new approaches to improve the prognosis of patients with Fabry cardiomyopathy are required. Methods and results: We generated induced pluripotent stem cell (iPSC) lines from a female patient and her son. Each iPSC clone from the female patient showed either deficient or normal GLA activity, which could be used as a Fabry disease model or its isogenic control, respectively. Erosion of the inactivated X chromosome developed heterogeneously among clones, and mono-allelic expression of the GLA gene was maintained for a substantial period in a subset of iPSC clones. Gb3 accumulation was observed in iPSC-derived cardiomyocytes (iPS-CMs) from GLA activity-deficient iPSCs by mass-spectrometry and immunofluorescent staining. The expression of ANP was increased, but the cell surface area was decreased in iPS-CMs from the Fabry model, suggesting that cardiomyopathic change is ongoing at the molecular level in Fabry iPS-CMs. We also established an algorithm for selecting proper Gb3 staining that could be used for high-content analysis-based drug screening. Conclusions: We generated a Fabry cardiomyopathy model and a drug screening system by using iPS-CMs from a female Fabry patient. Drug screening using our system may help discover new drugs that would improve the prognosis of patients with Fabry cardiomyopathy. Highlights: iPSC lines from a female Fabry patient have either normal/deficient GLA. Accumulation of Gb3 is observed in GLA-deficient iPS-CMs. ANP expression is increased even in ventricular-subtype of GLA-deficient iPS-CMs. High-content screening system for investigation of new Fabry drugs is established. Algorithm for selecting proper Gb3 staining is a key for accurate evaluation.